각막교정렌즈와 근시 조절 - 최혁진 (검안 및 콘택트렌즈 학회지, 23(4), 2024)
각막교정렌즈는 근시진행억제를 위한 효과적인 방법이다. 본고에서는 각막교정렌즈의 근시진행억제 원리와 무작위대조시험을 중심으로 현재까지 밝혀진 근시진행억제 효과를 알아보았다. 단기 효과에 대해서는 이견이 없는 듯 하나 장기적인 효과의 지속 여부와 렌즈 중단 후 발생하는 리바운드 현상에 대한 잘 설계된 연구가 필요하다. 또한 각막교정렌즈를 처방하는 의사나 환자 모두 감염성 각막염을 포함한 안전성에 대한 각별한 관심을 가져야 한다. Orthokeratology lenses are effective methods for controlling myopia progression. This paper describes the principles and effects of orthokeratology lenses, focusing on randomized controlled trials investigating their ability to prevent myopia progression. While the short-term effects are widely accepted, further well-designed studies are required to assess the persistence of long-term benefits and the possibility of a rebound phenomenon after lens discontinuation. Additionally, both physicians and patients should prioritize safety, particularly in preventing complications such as infectious keratitis. KCI Citation Count: 0